2019
DOI: 10.3390/ani9080489
|View full text |Cite
|
Sign up to set email alerts
|

Offal Chemical Composition from Veal, Beef, and Lamb Maintained in Organic Production Systems

Abstract: The aim of the study is to compare the content of nutrients, including selected macro- and micro-elements, in musculus semitendinosus and offal (liver, heart, kidneys, tongue, brain) derived from animals (calves, beef cattle, and lambs) that are fed and maintained in organic production conditions. The experimental material consisted of 60 animals: 20 calves, 20 beef cattle, and 20 lambs. This research was carried out using Limousin cattle and Ile de France sheep. From the obtained results, it is concluded that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 21 publications
5
39
1
Order By: Relevance
“…The variation patterns and ranges in liver fatty acid profiles in the present study were similar to previously reported findings [78][79][80][81][82][83]. The liver has also been reported to have a high nutrient content of essential amino acids, fatty acids, iron, zinc, magnesium, selenium, calcium, vitamins B1, B6, B12, and folic acid [84,85] and may explain why duck liver attracts a price premium and is consumed in France [86].…”
Section: Discussionsupporting
confidence: 89%
“…The variation patterns and ranges in liver fatty acid profiles in the present study were similar to previously reported findings [78][79][80][81][82][83]. The liver has also been reported to have a high nutrient content of essential amino acids, fatty acids, iron, zinc, magnesium, selenium, calcium, vitamins B1, B6, B12, and folic acid [84,85] and may explain why duck liver attracts a price premium and is consumed in France [86].…”
Section: Discussionsupporting
confidence: 89%
“…Moisture content of the muscles varies depending on the species, breed, age of animal, as well as its morphological-anatomical origin and nutrition of animal (Huff-Lonergan, 2010). Biel et al (2019) found in Musculus semitendinosus muscle moisture content of 67.67% in calves weighing 95 kg. High levels of nutrition, especially during the final phase, may increase the intramuscular fat content to a greater or lesser extent depending on the species, breed, age of the animals and other factors.…”
Section: Resultsmentioning
confidence: 99%
“…[123][124][125] The purported benefits of the carnivore diet may be attributed to the consumption of organ meats that contain highly bioavailable essential vitamins and minerals, such as iron, zinc, copper, selenium, thiamine, niacin, folate, vitamin B 6 , vitamin B 12 , vitamin A, vitamin D, vitamin K, and choline. [126][127][128] Other dietary compounds that have demonstrated benefit for skin health and are predominantly found in animal foods include carnosine, carnitine, creatine, taurine, coenzyme Q10, and collagen. [129][130][131][132][133][134] Nevertheless, there is no data to recommend the elimination of antioxidant-and micronutrient-dense plant-based foods.…”
Section: Carnivore Dietmentioning
confidence: 99%